Interpretation of measurements results of ice content in freezing mortars using DSC method - Stępień, Piotr; Rusin, Zbigniew; Świercz, Przemysław (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
The results of investigations of heat flows recorded at the low temperature differential scanning calorimeter (DSC) in the freezing cement mortars soaked with water are presented. Methods for extracting the thermal effects associated with the phase change of water as well as the methods for calculating the weight of ice with reference to the specific process temperature at which the phenomenon occurs are analyzed. It is found that computation assumptions and technical limitations of the calorimeter described in the technical literature can lead to significantly different results of determining the mass of formed ice.